SELEKSIBIAK Aspergillus spp. PENGHASIL AMILASE UNTUK PEMBUATAN PROTEIN SEL TUNGGAL DARITEPUNG GANYONG (Canna edulis Kerr.) - Elidar Naiola (BERITA BIOLOGI, 1998)
Two strains of fungi were used as innculant to produce Single Cell Protein (SCP) using the ganyong (Canna edulis Kerr.)starch as carbohydrate sources. Those two strains were Aspereillus nieer and A.clavatus identified as amylolytic fungi wich produce hight clear zone to colony diameter ratio in medium containing soluble starch with Iodium test.At the suitable interval time (0, 24, 48, 72 and 96 hours) the dry cell weight or biomass, pH and reducing sugar concentration in the medium containing ganyong starch was determined.It was found that maximum amount of reducing sugar concentration was hisher in A. clavatus (8.5 e/l) compared to A. nieer (4,5 g/l), were produced after 24 hours.The maximum amount of biomass produced by A. nieer was 8,5 g/l after 48 hr, while by A clavatus was 7,25g/l after 96 hr.